DEVELOPMENT OF DISCOVERY LEARNING-BASED STUDENT WORKSHEETS (LKPD) TO IMPROVE STUDENTS' ANALYTICAL SKILLS IN AL-QUR'AN HADITH SUBJECT ON THE TOPIC OF INFAK AND SADAQAH IN CLASS VIII-A AT MTsN 1 RANTAUPRAPAT - Fikri Ramadhan Tambak; Dedi Masri (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to develop Discovery learning-based Student Worksheets (LKPD) on the topic of